Efecto de extractos vegetales con solventes orgánicos de falso tabaco (nicotiana glauca) y jengibre (zingiber officinale), para el control de mosca blanca (bemisia tabaci) en condiciones de laboratorio. - Pullutasig López, Danilo Javier (2023)
Bemisia tabaci is a pest that can cause losses of up to 100% of production in solanaceae and cucurbits, due to its rapid dissemination in crops, which has forced farmers to take control measures based on frequent applications and excessive chemical products. The present investigation was carried out in the laboratory of the Technical University of Cotopaxi, and the objective was to evaluate the effect of plant extracts with organic solvents of false tobacco and ginger on whitefly at three concentrations of 25%, 50%, including the 0% control, where a Completely Random Design (DCA) was applied with an A*B factorial arrangement with six treatments and three repetitions, in each treatment 40 individuals of the species were released, where the plant extracts were applied. Mortality data collection was carried out by observation five minutes after having applied the treatments, using the counting and extraction of dead individuals. In the same way, the compositional analysis of the plant extracts under study was carried out through screening and gas chromatography. From the results obtained, it is prolonged that the compounds with the greatest presence are alkaloids, tannins or polyphenols and triterpenes, for False tobacco (Nicotiana Glauca) and unsaturated sterols, tannins or polyphenols and unsaturated sterols, for ginger (Zingiber officinale). It was established that the plant extracts control Bemisia tabaci under laboratory conditions, with an average of 23.66 individuals killed by Nicotiana Glauca. For the interaction between extracts*concentrations, Nicotiana Glauca, in a 50% concentration, presents an average of 29 dead individuals during the first five minutes of application of the extract.